Hospital rough cut capacity planning in a General Surgery service - Yasniel Sánchez Suárez; Maylín Marqués-León; Arialys Hernández-Nariño; Orlando Santos-Pérez (Dyna, 2023)
Hospital services constitute a fundamental pillar in the development of society. The objective of this article is to provide medium-term capacity planning improvements in a General Surgery service. A procedure was designed for capacity planning based on process analysis and design as well as the patients’ clinical characteristics. Some of the main results were: the demand of the Major Diagnostic Categories was predicted, the rooms were identified as the limiting resource in this kind of service, where an 82.82 % of them were used, the necessary wards reservations were calculated for the year 2021, with a rate of 163, 96 and 59 times for incisional, inguinal and umbilical hernia surgeries respectively, and a system of capacity improvement actions which were projected. The analysis of capacity using the proposed heuristic method makes possible to identify limiting resources, enhance performance and devise strategies to meet the demand.